Optimalisasi Peran Kader Posyandu Lansia dalam Pelayanan di Posyandu Edelweis - Hesty Hesty; Maimaznah Maimaznah; Muhammad Hidayat (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
The elderly population is currently increasing, therefore the government has formulated various health service policies for the elderly aimed at achieving a happy and efficient old age in family and community life in accordance with their existence. As a concrete manifestation of social and health services for the elderly, the government has launched services at the community level, namely the Elderly Integrated Service Post (Posyandu). The targets of the activities are cadres and the elderly. The aim is that cadres and the elderly can understand the health of the elderly and practice elderly exercise so that the optimization of the cadre's role can increase. The result of this community service is the increasing role of elderly posyandu cadres in health services at Posyandu Edelweis Thehok Village, Jambi City. This was achieved through survey approaches, education, giving booklets, and demonstrating elderly gymnastics to cadres and the elderly. In addition, the elderly Posyandu cadres are also able to provide better and more targeted health services to the elderly in the area and provide recommendations for improving health services for the elderly in other areas.